Improvement of National Beef Cattle Breeding System - Chalid Talib (WARTAZOA, Indonesian Bulletin of Animal and Veterinary Sciences, 2001)
Fulfillment of animal protein in Indonesia, come from animal products including fish i.e. meat, milk and egg. In the early of 1900 period beef cattle was a major product contributing to animal protein consumption but in the current decade poultry products come to replace it. Reformation in breeding strategy and its combination with feed conversion can enhance production efficiency and product number, maintain the continuity and the quality of products. These factors have not been included in a breeding plan for beef cattle, yet. The only appropriate breeding program is in Bali cattle that have not introduced feed intake and conversion into the planning. The ideal breeding program is to produce elite breeding stock and high quality of final stock from crossbreds that is labeled as a quality standard of the animal including recognized feed conversion and daily gain weight.   Key words: Improvement, breeding, beef cattle, national